Identificação de infecções simples e mistas de estirpes de Potato virus Y (PVY) em campos produtores de batata - Alves, Mirelly Caroline (2015)
The Potato virus Y (PVY) is considered the main virus with economic importance to potato culture in Brazil. One of the factors responsible for the increasing PVY diversity are mixed infections of strains that, during the viral replication process, can generate recombinants better adapted to environmental conditions with diverse biological, serological and molecular properties. In this paper, 126 tubers and 39 potato plant leaves infected with PVY, collected in commercial fields located in southern Minas Gerais were analyzed. Initially it was assessed the symptoms exhibited by plants from infected tubers and then DAS and TAS-ELISA, multiplex RT-PCR and RT-qPCR techniques were used to assess the occurrence and prevalence of PVY strains as well as their concentration in the sampled plants. In the plants originated from infected tubers, the symptoms vary from mild to severe in all potato cultivars, indicating a probable variability in the time cycle in which they were infected. In the TAS-ELISA serological testing, 46.1% of the samples showed serological behavior compatible with strains belonging to the 'O' serotype group and 34.5% with the ‘N’ group, while 23.9% were positive for mixed infections and 5.5% did not react with any of the tested monoclonal antisera. Among these, ten samples showed unusual serological pattern. In the multiplex RT-PCR test, the samples with O and N serotypes at the same time were identified as having mixed infection with PVYNTN and PVYN:O/N-Wi strains. Samples with O serotype were identified as PVYN:O/N-Wi and the ones with N serotype, as PVYNTN, except when they had mixed infections. It was identified 43,6% of PVYN:O/N-Wi, 37% of PVYNTN and 19,4% of mixed infections. One hundred and fifty-one samples were randomly selected for the RT-qPCR testing. The concentrations of PVYNTN strain in plants with mixed infections, regardless of its origin, varied from 2,79x107 to 2,79x1010 viral copies/µl, while the concentrations of PVYN:O/N-Wi were lower, ranging from 2,41x103 to 4,13x106 viral copies/µl. Sixty-one isolates showed typical profile of PVYNTN recombinant in RT-PCR multiplex and RT-qPCR. When subjected to RT-PCR for amplification of PVYE, 43 of them were positive, having a characteristic profile for this recombinant strain, although 9 isolates was also observed with atypical patterns for recombinant PVYE. The diversity of PVY isolates present in Brazilian fields of potatoes studied in this work, as well as the occurrence of mixed infections, provides a general epidemiological picture of this pathogen in the country.